Biosynthesis of Ribosomal RNA in Nucleoli Regulates Pluripotency and Differentiation Ability of Pluripotent Stem Cells. (26th November 2014) - Watanabe-Susaki, Kanako; Takada, Hitomi; Enomoto, Kei; Miwata, Kyoko; Ishimine, Hisako; Intoh, Atsushi; Ohtaka, Manami; Nakanishi, Mahito; Sugino, Hiromu; Asashima, Makoto; Kurisaki, Akira
Abstract: Pluripotent stem cells have been shown to have unique nuclear properties, for example, hyperdynamic chromatin and large, condensed nucleoli. However, the contribution of the latter unique nucleolar character to pluripotency has not been well understood. Here, we show that fibrillarin (FBL), a critical methyltransferase for ribosomal RNA (rRNA) processing in nucleoli, is one of the proteins highly expressed in pluripotent embryonic stem (ES) cells. Stable expression of FBL in ES cells prolonged the pluripotent state of mouse ES cells cultured in the absence of leukemia inhibitory factor (LIF). Analyses using deletion mutants and a point mutant revealed that the methyltransferase activity of FBL regulates stem cell pluripotency. Knockdown of this gene led to significant delays in rRNA processing, growth inhibition, and apoptosis in mouse ES cells. Interestingly, both partial knockdown of FBL and treatment with actinomycin D, an inhibitor of rRNA synthesis, induced the expression of differentiation markers in the presence of LIF and promoted stem cell differentiation into neuronal lineages. Moreover, we identified p53 signaling as the regulatory pathway for pluripotency and differentiation of ES cells. These results suggest that proper activity of rRNA production in nucleoli is a novel factor for the regulation of pluripotency and differentiation ability of ES cells. Stem Cells   2014;32:3099–3111